European Citizens' Consultations: Consultation begins at home. Issue 1 (April 2019) - Butcher, Paul; Pronckutė, Simona
In 2018 the European Citizens' Consultations took place throughout Europe. These events were organised by national governments and local actors, and thus represented a significantly increased role for the member states in communicating about Europe, a task which had previously been carried out chiefly by EU bodies. Thus, the Citizens' Consultations hold great potential for the application of the principle of subsidiarity to citizens' engagement and inclusion in decision-making. However, for the consultations to be successful, political leaders need to ensure that the results are reflected in the European Parliament election campaign and the agenda of the new leadership, demonstrating that citizens' voices are being heard in Brussels. This article will give background information about the European Citizens' Consultations, evaluate their potential and provide recommendations on how policymakers can ensure this new tool is used effectively.